Penguatan Simpul Desa Khaira Ummah Dalam Perintisan Yayasan Pendidikan Di Desa Pagak Kabupaten Malang - Pangestuti Prima Darajat; Urnika Mudhifatul Jannah; Zainal Abidin (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
ABSTRACT Kuliah Kerja Nyata Tematik (KKN-T) is a routine agenda of Universitas Islam Raden Rahmat in the context of community service to realize initiatives khaira ummah. Khaira ummah (best people) is the ideal form of Islamic society that has integrity of faith, orientation to humanity, and loyalty ti the truth. In 2021 KKN-T has the theme of strengthening and spreading the knots khaira ummah village. Dusun Sumbernongko one of the difficult to access hamlets in Pagak village. Seeing the importance of formal education needs for early childhood, community leaders initiated the establishment of educational foundations Raudlatul Atfhfal (RA). Learning is done simply, with 12 students and 2 teachers. Of cource, legality is needed to get access to funding and guidance from the government, in order to be able to organize advanced education. KKN-T group has program of providing learning facilities and assistance in managing the legality of the foundation, which is named the foundation Darul Dahlan Lil Ilmi Wal Irfan. Educational foundations based on khaira ummah are expected to strengthen the knot khaira ummah in Pagak village. KEYWORD: Educational Foundation, Khaira Ummah, Raudhatul Athfal